Expected closeness or mobilisation: why do voters go to the polls? : Empirical results for Switzerland, 1981 - 1999 - Gebhard Kirchgässner; Tobias Schulz (Center for Economic Studies and ifo Institute (CESifo), 2005)
Using data of Swiss referenda from 1981 to 1999, this paper presents new empirical results which allow us to discriminate better between the decision and mobilisation hypotheses of electoral participation. First, theoretical considerations which lead to these hypotheses are presented as well as the theory of expressive voting, and a survey of the available empirical evidence is given. Then, we describe the empirical approach before we come to its results. Those are much in line with the mobilisation but do not support the decision hypothesis. They are, however, also only partly compatible with the theory of expressive voting.
Keywords: D72; 330; expected closeness; expressive voting; campaign expenditure; turnout; direct democracy; Wahlverhalten; Wahlbeteiligung; Entscheidung; Referendum; Schätzung; Schweiz